RESPIRATORY VIRAL INFECTIONS IN CHILDREN AND ADOLESCENTS WITH HEMATOLOGICAL MALIGNANCIES - Seung Beom Han (Mediterranean Journal of Hematology and Infectious Diseases, 2019)
Abstract Background: Despite the introduction of a polymerase chain reaction (PCR) test for the diagnosis of respiratory viral infection (RVI), guidance on the application of this test and the management of RVI in immunocompromised children is lacking. This study evaluated the clinical characteristics of RVI and established strategies for the PCR test in children and adolescents with hematological malignancies. Methods: This study included children and adolescents with underlying hematological malignancies and respiratory symptoms, in whom a multiplex PCR test was performed. Patients in whom RVI was identified and not identified were categorized into Groups I and II, respectively. Group I was sub-divided into patients with upper and lower respiratory infections. The medical records of the enrolled patients were retrospectively reviewed. Results: A total of 93 respiratory illnesses were included. Group I included 46 (49.5%) cases of RVI, including 31 (67.4%) upper and 15 (32.6%) lower respiratory infections. Rhinovirus (37.0%) was the most common viral pathogen. Significantly more patients in Group I had community-acquired respiratory illnesses (p=0.003) and complained of rhinorrhea (p<0.001) and sputum (p=0.008) than those in Group II. In Group I, significantly more patients with lower respiratory infections had uncontrolled underlying malignancies (p=0.038) and received re-induction or palliative chemotherapy (p=0.006) than those with upper respiratory infections. Conclusions: A multiplex PCR test should be considered for RVI diagnosis in immunocompromised children and adolescents with respiratory symptoms, especially in those with rhinorrhea or sputum prominent over a cough. The early application of the PCR test in patients with uncontrolled underlying malignancies may improve outcomes.